(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
Medina 04020170120 : “This Reseacrh is aimed at students, especially law faculty students who want to carry out research related to Analysis of Unilateral Termination of Employment by Employers Based on Law Number 13 of 2003 concerning Employment (Case Study of Decision MANo.219 / Pdt.Sus-PHI / 2017 / Pn Mdn) This study seeks to reveal the consideration of the Panel of Judges in case study cases that occur in the field in accordance with the labor law and the government’s efforts in overcoming the problem of unilateral termination of employment by employers. The results of this study indicate that in the decision of the Industrial Relations Court at the Medan District Court Special Class IA with Decision Number 219 / Pdt.Sus-PHI / 2017 / Pn Mdn who tried the case in the first level court that the Defendant, namely PT Suzuki Finance Indonesia acted arbitrarily - because in terminating the work relationship unilaterally and contrary to the juridical requirements, namely Law Number 13 of 2003 concerning Manpower. As well as the efforts of the government as a regulator to create laws and regulations governing the issue of termination of employment must be strengthened and form a forum known as the Manpower Office to propose mediation regarding the issue of termination of employment”.